2024
DOI: 10.3389/fendo.2023.1285509
|View full text |Cite
|
Sign up to set email alerts
|

Association between neutrophil-to-lymphocyte ratio and diabetic kidney disease in type 2 diabetes mellitus patients: a cross-sectional study

Xiaowan Li,
Lanyu Wang,
Min Liu
et al.

Abstract: AimsThis investigation examined the possibility of a relationship between neutrophil-to-lymphocyte ratio (NLR) and diabetic kidney disease (DKD) in type 2 diabetes mellitus (T2DM) patients.MethodsAdults with T2DM who were included in the National Health and Nutrition Examination Survey (NHANES) between 1999 and 2020 were the subjects of the current cross-sectional investigation. Low estimated glomerular filtration rate (eGFR) (< 60 mL/min/1.73 m2) or albuminuria (urinary albumin-to-creatinine ratio (ACR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The above studies suggest that the SIRI is closely related to cardiovascular and cerebrovascular diseases. Two recent retrospective analyses of diabetic patients suggest that the SIRI is an independent risk factor for deteriorating kidney function [ 30 , 31 ]. In earlier studies, increased neutrophil and monocyte counts as well as decreased lymphocyte counts were associated with decreased kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…The above studies suggest that the SIRI is closely related to cardiovascular and cerebrovascular diseases. Two recent retrospective analyses of diabetic patients suggest that the SIRI is an independent risk factor for deteriorating kidney function [ 30 , 31 ]. In earlier studies, increased neutrophil and monocyte counts as well as decreased lymphocyte counts were associated with decreased kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al suggested that NLR might be an effective potential inflammatory marker for identifying the risk of diabetic kidney disease in T2DM patients in the United States. T2DM patients with elevated NLR levels should have their potential risk to kidney function closely monitored [ 47 ]. Studies have also found that NLR is highly valuable in diagnosing diabetic retinopathy [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These confounders included age, race, sex, marital status, family income to poverty ratio (PIR), and educational level, among other demographic factors. We also included a number of laboratory and anthropometric factors, including CVD, alcohol consumption, smoking status, total cholesterol (TC), triglycerides, aspartate aminotransferase (AST), alanine aminotransferase (ALT), blood uric acid, serum phosphorus, and body mass index (BMI) ( 7 , 15 17 ).…”
Section: Methodsmentioning
confidence: 99%